PROFIL BERPIKIR KREATIF SISWA KELAS AKSELERASI DALAM MEMECAHKAN MASALAH MATEMATIKA TERBUKA - Eni Eni Defitriani (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2014)
The background of the research is the needs of human resources that are able to think creatively in order to utilize and develop science and technology. One of the ways to overcome it is to optimize the improvement of students’ ability to think creatively in accelerated classes. Accelerated classes are accelerated learning program. Thus, the need of creative human resources can be immediately fulfilled. The aim of the research are to determine the students’ creativity and describe the process of students’ creative thinking in solving open mathematical problem. Creative thinking process is traced by referring to the stage of creative thinking by Wallas, namely preparation, incubation, illumination, and verification. This research is qualitative- descriptive. The research instruments used in the research were a problem-solving task sheet and in-depth interviews. The subjects in this research were students in accelerated classes in Jambi. Analysis of data used data analysis according to Miles and Huberman which consists of data reduction, exposure data and drawing conclusions. The results show that there are 8% of creative students from 25 students in accelerated class in solving open mathematical problems. Then 72% are less creative and 20% are not creative. In solving open mathematical problems, creative and less creative students pass through the four stages of creative thinking process by Wallas. Students who are not creative only pass through the three stages of creative thinking process which are preparation, incubation, and illumination.